Developing Reading Tasks for Autonomous Learning for Grade X Students of SMA 1 Sleman - Sungkawati Kardi Wahyuningsih; Joko Priyana (JOURNAL OF EDUCATION, 2013)
This research  study  was  aimed  at  developing  reading  tasks for autonomous  learning for  grade X students  of Senior High School 1 Sleman to  help   the  students   improve   their   reading   skills   independently.    This research  was a Research  and Development  study  that included  the steps  of needs    analysis,    course    grid    design,    product     development,    product validation,  product   revision,  try-out,  and study  of  the final  product.   This research developed five  units of reading tasks for  autonomous  learning.  The reading  tasks  were  developed  according  to  the  needs  analysis  data.  The need  of  grade  X  students   of  Senior  High  School 1 Sleman   in  learning reading  autonomously   is to  improve  their  reading  skills.  the  appropriate reading  tasks for  autonomous  learning are that they give clear instructions, describe  the  language  skills  clearly,  look  nice,  give  a  lot practice,   give feedback   and give  answers  or  let  the  learners  know  how  to complete  the tasks,  give  examples  and  tell  the  learners  how  to  learn  best.  The  needs related appropriate  reading tasks for  autonomous  learning  in terms of their components   that  are:  the  goal  of  learning   reading   autonomously   is  to improve the students'  reading skills;  the input presents  interesting pictures; the procedure  presents   interesting  and  enjoyable  activities;   the  learners' role is as the active reader; the teacher's  role is the feedback  giver; and the setting  is individual  work.  The components  of appropriate  reading  tasks for autonomous  learning  in terms of their organisations  are arranged  into four stages,   namely   introduction,   activities,   self-assessment,    and  check  your achievement.